HUBUNGAN TINGKAT PENGETAHUAN TERHADAP KEPATUHAN PENGOBATAN PADA PASIEN TUBERKULOSIS PARU DI RSUD KAB. BEKASI - Sari Dewi, Masita; Alaidarahman, Nazwa; Oktaviona, Nisa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
According to information contained in the 2023 Global TB Report, Indonesia is ranked second in the country with the highest number of TB cases in the world after India. The level of knowledge and compliance is an important indicator for assessing the success of treatment in pulmonary tuberculosis patients. This factor is one of the determinants of the increase or decrease in morbidity rates for pulmonary tuberculosis. The aim study was to determine the relationship between the level of knowledge and compliance with treatment of pulmonary tuberculosis patients at the Bekasi District Hospital. This research design a cross-sectional observational analytical descriptive approach carried out at the Bekasi District Hospital with sample of 146 respondents. Data collection used a validated knowledge level questionnaire and patient compliance with treatment used the MMAS-8 questionnaire. Data analysis was carried out with the SPSS statistical application using the chi-square test. Based on the research results, it is known that the p value (p=0.000) shows a relationship between the level of knowledge and treatment compliance in pulmonary tuberculosis patients at Bekasi District Hospital. The conclusion study is that there is a significant relationship between the level of knowledge and treatment compliance in pulmonary tuberculosis patients.